Activating the Cpx response induces tolerance to antisense PNA delivered by an arginine-rich peptide in Escherichia coli - Jakob Frimodt-Møller; Andreas Koulouktsis; Godefroid Charbon; Marit Otterlei; Peter E. Nielsen; Anders Løbner-Olesen (Elsevier, 2021)
Cell-penetrating peptides (CPPs) are increasingly used for cellular drug delivery in both pro- and eukaryotic cells, and oligoarginines have attracted special attention. How arginine-rich CPPs translocate across the cell envelope, particularly for prokaryotes, is still unknown. Arginine-rich CPPs efficiently deliver antimicrobial peptide nucleic acid (PNA) to its intracellular mRNA target in bacteria. We show that resistance to PNA conjugated to an arginine-rich CPP in Escherichia coli requires multiple genetic modifications and is specific for the CPP part and not to the PNA part. An integral part of the resistance was the constitutively activated Cpx-envelope stress response system (cpx∗), which decreased the cytoplasmic membrane potential. This indicates an indirect energy-dependent uptake mechanism for antimicrobials conjugated to arginine-rich CPPs. In agreement, cpx∗ mutants showed low-level resistance to aminoglycosides and an arginine-rich CPP conjugated to a peptide targeting the DNA sliding clamp, i.e., similar uptake in E. coli for these antimicrobial compounds.